The recent progress on silver nanoparticles: Synthesis and electronic applications - Bouafia, Abderrhmane; Laouini, Salah Eddine; Ahmed, Abdelaal S. A.; Soldatov, Alexander V.; Algarni, Hamed; Chong, Kwok Feng; Ali, Gomaa A. M. (MDPI AG, 2021)
Nanoscience enables researchers to develop new and cost-effective nanomaterials for energy, healthcare, and medical applications. Silver nanoparticles (Ag NPs) are currently increasingly synthesized for their superior physicochemical and electronic properties. Good knowledge of these characteristics allows the development of applications in all sensitive and essential fields in the service of humans and the environment. This review aims to summarize the Ag NPs synthesis methods, properties, applications, and future challenges. Generally, Ag NPs can be synthesized using physical, chemical, and biological routes. Due to the great and increasing demand for metal and metal oxide nanoparticles, researchers have invented a new, environmentally friendly, inexpensive synthetic method that replaces other methods with many defects. Studies of Ag NPs have increased after clear and substantial support from governments to develop nanotechnology. Ag NPs are the most widely due to their various potent properties. Thus, this comprehensive review discusses the different synthesis procedures and electronic applications of Ag NPs.